2023
DOI: 10.21203/rs.3.rs-2293229/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of femoral anteversion angle and neck-shaft angle on muscle forces and joint loading during walking

Abstract: Femoral deformities, e.g. increased or decreased femoral anteversion (AVA) and neck-shaft angle (NSA), can lead to pathological gait patterns, altered joint loads, and degenerative joint diseases. The mechanism how femoral geometry influences muscle forces and joint load during walking is still not fully understood. Hence, we conducted a comprehensive musculoskeletal modelling study to investigate the influence of femoral AVA and NSA on muscle forces and joint loads during walking. We created 25 musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Asymmetric HJCF can alter growth plate loading [ 19 ] and therefore lead to asymmetric development of bones in length and shape resulting in altered biomechanics. Previous studies showed that not only the subject-specific gait pattern but also the femoral geometry has a big impact on the estimation of the HJCF [ 16 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric HJCF can alter growth plate loading [ 19 ] and therefore lead to asymmetric development of bones in length and shape resulting in altered biomechanics. Previous studies showed that not only the subject-specific gait pattern but also the femoral geometry has a big impact on the estimation of the HJCF [ 16 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%